Pemanfaatan Rapor Pendidikan untuk Penguatan Literasi Numerasi Guru - Frida Maryati Yusuf; Nur Mustaqimah; Ilyas Husain; Zuliyanto Zakaria (Universitas Negeri Gorontalo, 2026)
Numeracy literacy is a fundamental competence that enables students to use mathematical concepts, procedures, facts, and tools in various life contexts. This community service activity aimed to strengthen teachers' initial understanding of the Education Report and data-based planning to support numeracy improvement. The activity was conducted on 8 May 2024 in the computer laboratory of SMP Negeri 1 Kabila Bone and involved 20 teachers. It consisted of preparation, material presentation, demonstration of indicator interpretation, discussion, and process evaluation. Participants actively discussed how to read achievement information, identify priority problems, reflect on possible root causes, and formulate follow-up actions through the Identify, Reflect, and Improve stages. The activity produced initial conceptual strengthening, but it did not measure changes in teachers' competence or students' numeracy outcomes. Continued mentoring, action-plan development, and measurable evaluation are therefore required.